Fulminant myocarditis: outcome predictors in an international cohort study - Majunke, Nicolas; Haertel, Franz; Binzenhöfer, Leonhard; Fischer, Natalie; Höpler, Julia; Scherzer, Marie; Hoffmann, Sabine; Scherer, Clemens; Lanz, Hugo; Hering, Daniel; Gade, Nils; Roden, Daniel; et al. (European heart journal, 2025)
Fulminant myocarditis (FM) is a complex clinical syndrome characterized by acute myocardial inflammation and cardiogenic shock. Evidence on long-term outcomes, mortality risk factors, and targeted treatment options remains limited.This retrospective analysis included consecutive adult patients admitted for FM between January 2012 and November 2022 at 26 European tertiary centres. According to endomyocardial biopsy (EMB) findings, patients were categorized as lymphocytic (LM), eosinophilic (EM), necrotizing eosinophilic (NEM), and giant-cell myocarditis (GCM) for the main analyses. Patients with inconclusive histopathology and those who did not undergo EMB were analysed separately. Primary outcomes were in-hospital and 1-year mortality. Multivariable logistic regression models were employed as generalized linear models to analyse the association of prespecified risk factors with mortality. Estimated associations are reported as odds ratios, generalized marginal effects, and adjusted prediction plots.A total of 271 patients [median age 43 years (interquartile range: 33-55 years), 58% male] were included in the analysis, of whom 146 fulfilled histopathologic criteria of LM (n = 99), EM (n = 18), NEM (n = 3), or GCM (n = 26). In the remaining 125 cases, EMB was inconclusive (n = 48) or not performed (n = 77). While there were no significant differences in cardiac arrest rate, admission Simplified Acute Physiology Score (SAPS) II, ventricular function, initial pH, and liver and kidney function parameters between histopathologic subgroups, the use of immunosuppressive medications and need for organ replacement varied. In the overall population, in-hospital and 1-year mortality were 31% and 34%, respectively. The highest 1-year mortality rate was observed among patients with GCM (LM: 25%, EM: 28%, NEM: 33%, GCM: 54%, P = .04). Patients who survived to discharge had an excellent functional outcome and long-term recovery of ventricular function. In total, 17 patients (6%) received a heart transplant during follow-up. Older age, lower pH, and histopathologic diagnosis of GCM were independently associated with in-hospital and 1-year mortality.In-hospital mortality among patients with FM remains high. Age, pH, and histopathological findings may serve as prognostic markers to identify high-risk patients and to guide treatment strategies. Long-term outcomes are excellent among those who survive to discharge.